Dispersion and microwave processing of nano-sized ITO powder for the fabrication of transparent conductive oxides. Issue 16 (December 2016) - Ghanizadeh, S.; Peiris, T.A. Nirmal; Jayathilake, D.S.Y.; Hutt, D.A.; Wijayantha, K.G.U.; Southee, D.J.; Conway, P.P.; Marchand, P.; Darr, J.A.; Parkin, I.P.; Carmalt, C.J.
Abstract: Aqueous dispersions of tin-doped indium oxide (ITO) nanopowder were prepared and the effect of the addition of PEG 400, Tween 80 and β-alanine as dispersants was investigated using zeta potential and particle size distribution measurements. Both PEG 400 and β-alanine were found to produce stable dispersions that were used to deposit ITO thin films on glass substrates by dip and spin coating methods. The ITO thin films were heat-treated using both conventional and microwave heat treatment in order to improve the inter-particle connections and hence the resistivity and transparency of the films. All the films exhibited an average transmittance of >80% over the visible spectrum after being subjected to the heat treatment process. ITO films prepared with no dispersant showed very high resistivity values for both heating methods, however addition of 2 wt% PEG 400 to the dispersion yielded a reduction in the resistivity values to 1.4×10 −1 Ω cm and 3.8×10 −2 Ω cm for conventionally and microwave treated films, respectively. The surface morphological studies confirmed that addition of dispersants improved the film uniformity and inter-particle connections of the ITO films considerably.